Whole-exome sequencing reveals common and rare variants in immunologic and neurological genes implicated in achalasia - Li, Quanlin; Chen, Weifeng; Wang, Cheng; Liu, Zuqiang; Gu, Yayun; Xu, Xiaoyue; Xu, Jiaxing; Jiang, Tao; Xu, Meidong; Wang, Yifeng; Chen, Congcong; Zhong, Yunshi; et al. (American journal of human genetics, 2021)
Idiopathic achalasia (IA) is a severe motility disorder characterized by neuronal degeneration in the myenteric plexus, but the etiology remains largely unknown. We performed whole-exome sequencing (WES) in 100 IA-affected individuals and 313 non-IA control subjects and validated the results in 230 IA-affected individuals and 1,760 non-IA control subjects. Common missense variants rs1705003 (CUTA, GenBank: NC_000006.11:g.33385953A>G) and rs1126511 (HLA-DPB1, GenBank: NC_000006.11:g.33048466G>T) at 6p21.32 were reproducibly associated with increased risk of IA (rs1126511: OR = 1.83, p = 2.34 × 10−9; rs1705003: OR = 2.37, p = 3.21 × 10−7), meeting exome-wide significance. Both variants can affect the expression of their target genes at the transcript level. An array-based association analysis in 280 affected individuals and 1,121 control subjects determined the same signal at 6p21.32. Further conditional analyses supported that the two missense variants identified in WES-based association study were potential causal variants of IA. For rare variants, the top genes identified by gene-based analysis were significantly enriched in nerve and muscle phenotypic genes in the mouse. Moreover, the functional rare variants in these genes tended to cooccur in IA-affected individuals. In an independent cohort, we successfully validated three rare variants (CREB5, GenBank: NC_000007.13:g.28848865G>T; ESYT3, GenBank: NC_000003.11:g.138183253C>T; and LPIN1, GenBank: NC_000002.11:g.11925128A>G) which heightens the risk of developing IA. Our study identified and validated two common variants and three rare variants associated with IA in immunologic and neurological genes, providing new insight into the etiology of IA.